The interplay of personality and attitudes toward own aging across two decades of later life - Kornadt, Anna Elena; Siebert, Jelena Sophie; Wahl, Hans-Werner (PLOS ONE, 2019)
Big Five personality traits are assumed to be linked with attitudes toward own aging. Since both constructs have central importance for the aging process, it is surprising that to our knowledge no study so far comprehensively addressed their mutual connection over time. We used data from the ILSE study, a longitudinal study capturing personality and attitudes toward own aging at four measurement occasions, spanning 20 years and including two participant cohorts in midlife (n = 501; born 1950-52) and later life (n = 500; born 1930-32). Dual latent change score models showed that personality was longitudinally related to change in attitudes toward own aging: Lower Neuroticism, higher Conscientiousness, and higher Openness predicted more positive attitudes, whereas the direction of the effect for Extraversion varied by time. Furthermore, the role of personality seems to be confined to certain sensitive periods in midlife and early old age. Contrary to our expectations, attitudes toward own aging had only marginal longitudinal impact on the Big Five. Our results shed light on the developmental co-dynamics of personality and subjective perceptions of aging across the second half of the lifespan.
Gesehen am 04.06.2020